Ultrastructural immunolocalization of nestin in the regenerating tail of lizards shows its presence during cytoskeletal modifications in the epidermis, muscles and nerves. Issue 2 (April 2015) - Alibardi, Lorenzo
Highlights: Immunogold localization of nestin in lizard keratinocytes, nerves and myotubes. Keratinocytes contain nestin associated to desmosomes likely connected to elasticity. In myotubes nestin is associated to sarcomere formation. In nerves nestin is present around neurotubules/neurofilaments likely connected to axon growth. Nestin localization appears related to cytoskeletal remodeling in regenerating tissues. Abstract: Nestin has been considered a neural stem cell marker, and represents an intermediate filament protein likely involved in restructuring the cytoskeleton in different cell types. The present ultrastructural study has immunodetected nestin especially in the wound epidermis, regenerating myotubes and in the growing nerves of the regenerating tail of lizards. In keratinocytes of the stratified wound epidermis nestin is present in the irregular electron-paler meshwork located along the cell perimeter and among keratin bundles converging into desmosomes. In the regenerating muscles nestin-immunoreactivity remains confined to some external regions along the myotubes and in the cytoplasmic ends of the myotubes not occupied by myofibrils. A diffuse nestin immunolabeling is also present among the neurofilaments of growing axons, in Schwann cells and in ependymal cells of the regenerating spinal cord of the tail. The localization of nestin in sites of cytoskeletal remodeling in keratinocytes, myotubes, ependymal cells and axons, suggests that this protein is associated to the reassembling of keratin tonofilaments in moving keratinocytes, assembling of contractile proteins in myotubes, and in the organization of neurofilaments during the growth and myelination of axons within the regenerating lizard tail.